Good news or bad news? The impact of information valence on high school students’ willingness to share misinformation and the effectiveness of a targeted accuracy prompt - Wang, Zhichao; Jin, Hua; Li, Shanshan (Frontiers in Psychology, 2025)
BackgroundWith the rapid proliferation of misinformation on social media, increasing attention has been paid to its psychological and behavioral mechanisms. Emotional valence—particularly the positive or negative tone of information—is often used in constructing misinformation, facilitating its wide dissemination. However, existing findings on how emotional valence influences misinformation sharing remain mixed, especially among adolescent populations. This study explores the impact of information valence on high school students’ willingness to share misinformation and evaluates the effectiveness of a targeted accuracy prompt.MethodsTwo experiments were conducted. In Experiment 1, 53 high school students completed a news-sharing task involving both true and false headlines with varying emotional valence. Their willingness to share was measured. In Experiment 2, 40 students received a valence-targeted accuracy prompt designed to highlight common characteristics of misinformation. The effectiveness of the intervention in reducing misinformation sharing was then assessed.ResultsExperiment 1 showed that participants were significantly more willing to share positive misinformation than negative misinformation, regardless of authenticity. Information valence had a significant effect on response bias. In Experiment 2, students who received the accuracy prompt intervention demonstrated significantly lower willingness to share misinformation compared to the control group, indicating the effectiveness of this brief and targeted approach.ConclusionInformation valence plays a critical role in shaping adolescents’ willingness to share misinformation, with positive content being more readily shared. A brief accuracy prompt intervention tailored to information characteristics and emotional valence can effectively reduce misinformation sharing among high school students. These findings provide theoretical and practical insights into combating misinformation in adolescent populations.